2021
DOI: 10.3389/fevo.2021.751072
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Light at Night Is Phase Dependent: A Study on Migratory Redheaded Bunting (Emberiza bruniceps)

Abstract: Artificial light at night (LAN) alters the physiology and behavior of an organism; however, very little is known about phase-dependent effects of LAN, particularly, in night migratory songbirds. Therefore, in this study, we investigated whether the effects of LAN on daily activity and photoperiodic responses in the Palearctic Indian migratory songbird, redheaded buntings (Emberiza bruniceps), is dependent on the different phases of the night. Male buntings maintained under short photoperiod (8L:16D; L = 100 lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
(84 reference statements)
3
11
1
Order By: Relevance
“…The phase‐dependent response of melatonin secretion provides valuable insights into the underlying mechanisms of how ALAN affects cues for the timings of biological processes (Bedrosian & Nelson, 2017; Gaston et al., 2017), where the early night may be perceived as an extension of ‘subjective’ dusk and late‐night as ‘subjective’ early dawn. This interpretation is supported by the behavioural changes observed in buntings ( Emberiza bruniceps ), which extend their daytime activity into the early night and advance the onset of daytime activity into the late night when exposed to ALAN (Kumar et al., 2021).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The phase‐dependent response of melatonin secretion provides valuable insights into the underlying mechanisms of how ALAN affects cues for the timings of biological processes (Bedrosian & Nelson, 2017; Gaston et al., 2017), where the early night may be perceived as an extension of ‘subjective’ dusk and late‐night as ‘subjective’ early dawn. This interpretation is supported by the behavioural changes observed in buntings ( Emberiza bruniceps ), which extend their daytime activity into the early night and advance the onset of daytime activity into the late night when exposed to ALAN (Kumar et al., 2021).…”
Section: Discussionmentioning
confidence: 86%
“…First, we can tune the spectral composition of artificial light sources used at night to minimize the proportion of blue light (Gaston & Sánchez de Miguel, 2022), because our meta‐analytic finding confirmed that short wavelengths (blue portion) suppress melatonin levels more than other wavelengths across species. Second, we can adopt a discontinuous lighting strategy (Kumar et al., 2021), such as using motion sensors to turn lights on or higher only when necessary and avoiding artificial lighting during midnight hours. Third, we should reduce the light intensity of all types of artificial light to mitigate the impact on melatonin suppression (Agathokleous, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…5–5.0 lux) in great tits [133], European blackbirds [66] and zebra finch [134]. Importantly, as expected for a circadian mechanism, the melatonin response to part-time ALAN was phase-specific, as shown in a study of migratory red-headed buntings ( Emberiza bruniceps ) [135].…”
Section: Impacts Of Light Pollution On Birdsmentioning
confidence: 96%
“…The annual change in daylength is the predominant predictive cue that birds used to time seasonal rhythms (Dawson, 2001; Tolla & Stevenson, 2020). Of all the avian models currently in use for the study of photoperiod and reproductive development, few are more studied than Japanese quail ( Coturnix japonica ) and migratory buntings (Huss et al, 2008; J. Kumar et al, 2021). Japanese quail show incredibly robust changes in reproductive physiology and in their neuroendocrine response to increased photoperiod (Stevenson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…development, few are more studied than Japanese quail (Coturnix japonica) and migratory buntings (Huss et al, 2008;J. Kumar et al, 2021).…”
mentioning
confidence: 99%